P28 HPV/p16 positivity is associated with improved survival in oropharyngeal cancer patients treated with postoperative radiotherapy. Issue 5 (May 2015) - Heiduschka, G.; Grah, A.; Oberndorfer, F.; Kadletz, L.; Altorjai, G.; Kornek, G.; Wrba, F.; Thurnher, D.; Selzer, E.
Abstract : Introduction: In the literature, HPV-infection and/or p16 positivity have been consistently demonstrated to correlate with improved response rates in oropharyngeal squamous cell carcinoma (OPSCC) patients treated with primary radiotherapy (RT) alone as well as in combination with chemotherapy. However, the exact role of HPV/p16 positivity in patients treated with postoperative RT is still unclear. Material and methods: We analyzed tumor samples for HPV-DNA and p16 expression and correlated these variables with treatment outcome in a series of 63 consecutively treated oropharyngeal cancer patients (95% stage III/IV). HPV and p16 analysis was performed using validated test systems. Survival was estimated by the Kaplan-Meyer method. Cox-proportional-hazard regression models were applied to compare the risk of death among patients stratified according to risk factors. Results: Expression of p16 or high-risk HPV-DNA was detected in 60.3% and 39.6% of the tumors, respectively. p16 expression (overall survival (OS) at 2-years of 91%) as well as HPV-infection (OS at 2-years of 95%) was associated with improved OS. Mean survival in p16 positive patients was 112 months compared to 64.6 months in case of p16 negativity. All HPV positive tumors stained positive for p16. In a multivariable analysis, p16 positivity was associated with improved OS as well as with disease-free survival. Conclusion: P16 expression as well as HPV infection is strongly associated with the outcome of postoperatively irradiated OPSCC patients. HPV and p16 double negative OPSCC patients should be regarded as a distinct "very high-risk" patient group that may benefit from intensified or novel treatment combinations.